Food and feeding habits of the seahorses Hippocampus spinosissimus and Hippocampus trimaculatus (Malaysia). (17th November 2014) - Yip, M.Y.; Lim, A.C.O.; Chong, V.C.; Lawson, J.M.; Foster, S.J.
Abstract : Two seahorse species, Hippocampus spinosissimus and Hippocampus trimaculatus, sampled in east and west coastal waters of Peninsular Malaysia, fed mostly on crustacean prey; small caridean shrimps and amphipods as adults (both species), and copepods and larval meroplankton as juveniles (for H. trimaculatus only). The similar short relative gut length (~0.4) of both species is consistent with a carnivorous diet. Both species are considered specialists in prey selection, focusing on slow-moving epibenthic, hyperbenthic and canopy-dwelling crustaceans that dwell on the mud-sand seabed, or are associated with seagrass or mangrove areas. In this light, seahorses with their juveniles in shallow waters are vulnerable to coastal reclamation and development.